Asymmetric Coplanar F-strip Fed Antenna for Dual Band Wireless Applications - Ansal Kalikuzhackal Abbas; Thangavelu Shanmuganatham (International Journal of Electrical and Computer Engineering (IJECE), 2015)
A compact planar antenna for dual band applications is presented in this paper. The proposed antenna has Dumbbell shaped defect on the ground plane and it is fed by Asymmetric coplanar strip(ACS). The antenna is printed on FR4 epoxy substrate and it has a compact size of 21× 19 × 1.6 mm3. The antenna exhibits a dual band of resonances at 3.4GHz and 5.5 GHz which is used for WiMAX/WLAN. The planar design, simple feeding techniques and compactness make it easy for the integration of the antenna into circuit boards. Details of the antenna design and simulated results are presented and discussed. Simulation tool, based on the method of moments (Mentor Graphics IE3D version 15.10) has been used to analyze and optimize the antenna. Various features such as compactness, simple con-figuration and low fabrication cost make the antenna is suitable for dual band wireless applications.